The UTN program - Patrizia Rossi (Electronica, 2001)
We give an algorithm which goal is to find the energy barrier between a given pair of points in a graph which represents the conformational space of a molecule. If the conformational space is homeomorphic to an -dimensional torus, then the graph can be chosen of a particular form. The UTN software, which implements the algorithm in this case, is described in detail. Finally we focus on applications: to show how UTN works, some examples are carried on in detail, with the additional support of graphical animation1 in the twodimensional case. The source code of the program and some data of the examples are available to the reader.